552 NON-ALCOHOLIC FATTY LIVER DISEASE AND THE HEPATIC RESPONSE TO SURGERY AMONG PATIENTS WITH ESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Donlon, Noel; Elliott, Jessie A; Doyle, Suzanne L; King, Sinead; Beddy, Peter; Moran, Brendan; Donohoe, Claire; Ravi, Narayanasamy; Reynolds, John V
Abstract: : Visceral obesity, metabolic syndrome and non-alcoholic fatty liver disease (NAFLD) represent risk factors for esophageal adenocarcinoma (EAC). The prevalence of NAFLD, and its impact on the hepatic response to esophageal cancer surgery, has never been systematically evaluated, and was the focus of this study. Methods: Consecutive patients (n = 547) treated with curative intent for esophageal cancer from 2007–2017 were studied. In an unselected subgroup (n = 138), liver biopsies were collected intraoperatively and assessed for NAFLD, defined as ≥5% macrovesicular steatosis. Postoperative complications were recorded prospectively, including Clavien-Dindo grade (CD) and comprehensive complications index (CCI). Liver function tests were monitored in the first postoperative week, with hepatocellular dysfunction defined as a transaminase rise ≥3-times the upper limit of normal. Multivariable logistic and Cox proportional hazards regression were utilised to determine independent predictors of operative and oncologic outcome. The study was registered on clinicaltrials.gov (NCT04152044). Results: NAFLD was evident in 62 patients (47.7%) who had biopsies, with a mean (SD) score of 10.1(9.3)%. NAFLD was associated with metabolic syndrome (41.9 vs 25%, P = 0.04), obesity (44.1 vs 11.9%, P < 0.001) and visceral adiposity (172.8 vs 136.5 cm2, P = 0.008), but not clinical or pathologic disease stage. Postoperative hepatocellular dysfunction was observed in 287 (54.8%) patients, associated with NAFLD (P = 0.006), but not visceral obesity (P = 0.396), and normalized in a median (range) of 9 (1–76) days. NAFLD did not impact oncologic outcome, but postoperative hepatocellular dysfunction was independently associated with reduced overall survival (HR 1.87 (1.16–2.29), P = 0.002) on multivariable analysis. Conclusion: A marker of metabolic dysregulation in obesity-associated carcinogenesis, NAFLD is prevalent among patients with esophageal cancer. Liver dysfunction post esophagectomy is common, and although temporary, is associated with worse oncologic outcomes. Baseline NAFLD did not incur an adverse long-term oncologic outcome.